2022
DOI: 10.3389/fimmu.2022.1024931
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of core immune-escape genes highlights LCK as an immune-related prognostic biomarker in melanoma

Abstract: The tumor microenvironment is complicated and continuously evolving. This study was devoted to the identification of potential prognostic biomarkers based on the tumor microenvironment associated with immunotherapy for melanoma. This study integrates a couple of melanoma single cell and transcriptome sequencing datasets and performs a series of silico analyses as nicely as validation of molecular biology techniques. A core set of immune escape related genes was identified through Lawson et al. and the ImmPort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…T cells are important effectors for the immune system to exert antitumor effects. Cytotoxic T lymphocytes, also known as CD8 + T cells, play a crucial role in the antitumor cellular immune response. , CD4 + T cells have various subtypes, can secrete cytokines, and have regulatory effects on antitumor immunity. Some clinical studies have also found that CD4 + T cells can secrete key molecules related to cell lysis particles, which have direct cytotoxic effects .…”
Section: Resultsmentioning
confidence: 99%
“…T cells are important effectors for the immune system to exert antitumor effects. Cytotoxic T lymphocytes, also known as CD8 + T cells, play a crucial role in the antitumor cellular immune response. , CD4 + T cells have various subtypes, can secrete cytokines, and have regulatory effects on antitumor immunity. Some clinical studies have also found that CD4 + T cells can secrete key molecules related to cell lysis particles, which have direct cytotoxic effects .…”
Section: Resultsmentioning
confidence: 99%
“…Then this study evaluated the response of COAD patients to immunotherapy. It has been reported that the immune system plays an important role in the progression and treatment of cancer, and the presence of tumor immune escape protects tumor cells from the attack of the immune system [ 36 , 37 ]. Differentiation clusters, as markers of immune cells, such as CTLA-4, CD25, and PD-1, have been identified as potential immunotherapy targets for malignant tumors in recent years [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, immunotherapy for cancer treatment has been gaining increased attention [ 12 16 ]. Several researchers have discovered that blockers of cytotoxic T lymphocyte-associated antigen 4, programmed cell death-ligand 1, and programmed cell death-1 elicit anti-cancer effects on HCC cells [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%